2011
DOI: 10.1530/eje-10-1039
|View full text |Cite
|
Sign up to set email alerts
|

Lipid accumulation product: a powerful marker of metabolic syndrome in healthy population

Abstract: Objective: The metabolic syndrome (MS) is a cluster of cardiometabolic factors, which predisposes to diabetes and cardiovascular disease (CVD). Early detection of high-risk individuals for MS using accurate measures of insulin resistance (IR) could improve detection and prevention of CVD and diabetes. The aim of this study was to explore the ability of lipid accumulation product (LAP), compared with traditional measures of IR, to identify MS. Design: In total, 768 Spanish adults were recruited. MS was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 26 publications
9
99
0
4
Order By: Relevance
“…23 Therefore, increased LAP may indicate ectopic lipid deposition and reflect lipid overaccumulation. 12,14 It suggested that in both the cross-sectional study and the prospective study, LAP was an effective index for assessing the risk of CVD and diabetes. Previous studies found that LAP outperformed BMI and WC in identifying metabolic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Therefore, increased LAP may indicate ectopic lipid deposition and reflect lipid overaccumulation. 12,14 It suggested that in both the cross-sectional study and the prospective study, LAP was an effective index for assessing the risk of CVD and diabetes. Previous studies found that LAP outperformed BMI and WC in identifying metabolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…LAP was closely associated with CVD, diabetes and metabolic syndrome and outperformed BMI for identifying these diseases. 8,[12][13][14] In polycystic ovary syndrome patients, LAP was an effective index with higher sensitivity and specificity than BMI and WC for predicting CVD. 13 Although there were some studies on the correlation between LAP and CVD, diabetes in European subjects, there have been few studies looking at the correlation between LAP and IR in Asian cohort.…”
Section: Introductionmentioning
confidence: 97%
“…3 Most of the studies analysed evaluated a mixed population, stratified by sex and/or age range. The cut-off point for LAP suggested by the authors [22][23][24][25][26] varied from 31.6 to 51.8, with a difference between the sexes (Table 4). Among men, the LAP AUC to predict MetS varied from 0.84 to 0.937, while for women the lowest AUC was 0.78 and highest was 0.904 (Table 4).…”
Section: Anthropometric Indicatorsmentioning
confidence: 99%
“…An assay published by Taverna et al [39] in healthy Argentine males, LAP showed an area under the highest curve even than other IR variables, such as HOMA-IR and QUICKI, whereby LAP has been associated with lipolysis of visceral compartment, which is considered by De Fronzo to be the beginning of the cascade of changes that characterize the pathophysiology of IR [40]. By evaluating individually, the components of the MetS, the VAI and LAP indexes were correlated with better precision with the value of WC and triglycerides; To measure the risk of MetS (Figure 3, Figure 4, Figure 5 and Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Although explanations for this observation have not yet been elucidated, it is likely to be related to differences in the regional distribution of adipose tissue by sex as well as patterns of visceral fat deposition. In addition, in fact, men have, on average, more visceral fat and less subcutaneous fat [39]. In our results, the LAP index was the parameter with the highest sensitivity discriminating individuals with and without MetS in the ROC curve, with AUC 0.9489 ( Figure 7 and Figure 8), which is consistent with several population studies conducted in individuals from China [41,42] and Iran, which showed the same conclusions [29], similarly to Abruzzese et al [43] in a population of Latin America, found similar results, with similar cutoff points for different populations and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%